Examination of the relationship between peak linear and angular accelerations to brain deformation metrics in hockey helmet impacts - Post, A.; Oeur, A.; Hoshizaki, B.; Gilchrist, M. D. (Computer Methods in Biomechanics and Biomedical Engineering, 2011)
Ice hockey is a contact sport which has a high incidence of brain injury. The current methods of evaluating protective devices use peak resultant linear acceleration as their pass/fail criteria, which are not fully representative of brain injuries as a whole. The purpose of this study was to examine how the linear and angular acceleration loading curves from a helmeted impact influence currently used brain deformation injury metrics. A helmeted Hybrid III headform was impacted in five centric and non-centric impact sites to elicit linear and angular acceleration responses. These responses were examined through the use of a brain model. The results indicated that when the helmet is examined using peak resultant linear acceleration alone, they are similar and protective, but when a 3D brain deformation response is used to examine the helmets, there are risks of brain injury with lower linear accelerations which would pass standard certifications for safety.